Exploring Factors Affecting Students’ Intrinsic and Extrinsic Motivation in Learning English at SMPIT Al-Fityan School Gowa - Bismayanti, Bismayanti; Sakkir, Geminastiti; Aeni, Nur (Journal of Excellence in English Language Education, 2024)
This research aims to determine factors affecting students’ intrinsic and extrinsic motivation in learning English at SMPIT Al-Fityan School Gowa. The researcher applies mixed-methods research to achieve the research objectives. The data was collected in the form of a questionnaire and an interview. The subjects of this study were eighth-grade students of SMPIT Al-Fityan School Gowa. The sample of the questionnaire had 52 students and the interviews were with 6 students who were taken using a purposive sampling technique. The results of the data analysis showed that students of SMPIT Al-Fityan School Gowa have high motivation and the dominant affecting factor of students’ motivation in learning English at SMPIT Al-Fityan School Gowa is intrinsic motivation. The intrinsic factors that affect students’ motivation are curiosity, control, competition, and cooperation.